Determinants of foreign direct investment into the ASEAN-5 nations and China - Goh, Qianning (2008)
This report covers an analysis of several economic variables affecting the amount of inward foreign direct investment (FDI) for 5 ASEAN nations - namely Indonesia, Malaysia, the Philippines, Singapore and Thailand - and China. A discussion of these selected variables serves to explain how these are expected to affect inward FDI for the countries in the study. After looking at the results of the regression analysis conducted, the report concludes with a look at the implications of the findings of the project.